Dealcoholized silicone sealant capable of being rapidly cured at initial stage and preparation method of dealcoholized silicone sealant
By using metal organic framework MIL-101 to modify CaCO3 and alkoxy-terminated polydimethylsiloxane, the diffusion rate of water vapor in the filler is improved, and the problem of slow curing speed of traditional silicone sealants is solved, and the problem of slow curing speed of traditional silicone sealants is achieved. The effect of achieving a curing depth of 1mm within 6 hours and a depth of 3.5mm within 24 hours is met, meeting the needs of construction speed and mechanical strength.
Patent Information
- Application Number
- CN202411363105.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The initial curing speed of traditional dehydrogenated silicone sealants is slow and cannot meet the high requirements of construction speed. Especially in application scenarios such as doors and windows, photovoltaic modules and curtain walls, faster curing speed is required to facilitate the subsequent process.
Modified CaCO3 with metal organic framework MIL-101 and combined with alkoxy-terminated polydimethylsiloxane, the initial rapid curing is prepared by increasing the migration rate of water vapor inside the filler, while ensuring mechanical strength. Dealcohol silicone sealant.
At 25°C and 30% relative humidity, the diffusion coefficient of water vapor in the filler was greatly increased by 3600%, the curing depth reached more than 1 mm in 6 hours, and the curing depth reached more than 3.5 mm in 24 hours, meeting the requirements of construction speed and mechanical strength.
Smart Images

Figure BDA0005065415050000071 
Figure BDA0005065415050000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealants, and in particular to an initial fast-curing dealcoholized silicone sealant and a preparation method thereof. Background Art
[0002] Dealcoholized silicone sealant has good adhesion to glass, stone, plastic, metal and other substrates, and is non-corrosive to metal substrates, so it is widely used in the fields of door and window waterproofing, curtain wall weatherproof sealing, and electronic and electrical sealing. With the continuous improvement of upstream and downstream technologies in the industrial chain, the requirements for construction speed are getting higher and higher. The next process must be started 6 to 8 hours after gluing. For example, doors and windows must be turned over within 6 hours after gluing, photovoltaic modules must be squeezed within 6 hours after gluing, and aluminum curtain walls must have relatively large displacements within 8 hours after gluing. These changes in application scenarios have put forward higher requirements for the initial curing speed of sealants.
[0003] Dealcoholized silicone sealants require water vapor in the air to react in order to crosslink and cure, forming a three-dimensional network structure and having a sealing function. After the surface of traditional dealcoholized silicone sealants is cured, the rate at which water vapor penetrates into the inner layer of the sealant drops sharply, resulting in a slow deep curing rate of the dealcoholized silicone sealant, which often requires 24 hours to meet the curing requirements of the application scenario. Summary of the invention
[0004] Based on this, it is necessary to provide a dealcoholized silicone sealant with a faster initial curing speed and higher mechanical strength.
[0005] A method for preparing a dealcoholized silicone sealant with rapid initial curing comprises the following steps:
[0006] The metal organic framework MIL-101, silane coupling agent and calcium carbonate are dispersed in an organic solvent, and then the temperature is raised to 140-160°C for reaction for 5-7 hours to obtain MIL-101@CaCO3;
[0007] According to the mass parts, 100 parts of α, ω-dihydroxy polydimethylsiloxane, 20 to 30 parts of alkoxy-terminated polydimethylsiloxane, 100 to 120 parts of MIL-101@CaCO3, 15 to 30 parts of cross-linking agent, 2 to 8 parts of coupling agent and 0.1 to 1 part of catalyst are mixed and dispersed to obtain the dealcoholized silicone sealant.
[0008] In one embodiment, the mass ratio of MIL-101, silane coupling agent and calcium carbonate is 4:0.5-1.5:4-6. Preferably, the mass ratio of the three is 4:1:6.
[0009] In one embodiment, the alkoxy-terminated polydimethylsiloxane is selected from one or more of methoxy-terminated polydimethylsiloxane and ethoxy-terminated polydimethylsiloxane.
[0010] In one embodiment, the viscosity of the α,ω-dihydroxy polydimethylsiloxane is 2000-20000 cps, and the viscosity of the alkoxy-terminated polydimethylsiloxane is 100-350 cps.
[0011] In one of the embodiments, the preparation method of MIL-101 comprises the following steps: dissolving 10 parts of chromium nitrate and 4 parts of terephthalic acid in water by mass, adding 6 parts of hydrofluoric acid, heating to 210-230 degrees and reacting for 7-9 hours to obtain MIL-101.
[0012] In one embodiment, the D50 of the calcium carbonate is 100-200 nm and the specific surface area is 22-25 m 2 / g.
[0013] In one embodiment, the crosslinking agent is selected from one or more of methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane and vinyltriethoxysilane.
[0014] In one embodiment, the coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(-β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-glycidyl ether propyltrimethoxysilane, γ-glycidyl ether propyltriethoxysilane, epoxycyclohexyltrimethoxysilane, epoxycyclohexyltriethoxysilane, mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, isocyanatetrimethoxysilane and isocyanatetriethoxysilane.
[0015] In one embodiment, the catalyst is selected from one or more of tetraisopropyl titanate, tetrabutyl titanate, diisopropoxybis(ethoxyacetoacetyl)titanium, di-n-butoxybis(ethoxyacetoacetyl)titanium and 1,3-dipropoxybis(ethoxyacetoacetyl)titanium.
[0016] The present invention also provides a dealcoholized silicone sealant with rapid initial curing, which is prepared according to the above preparation method.
[0017] The above solution of the present invention has the following beneficial effects:
[0018] The present invention provides a dealcohol-type silicone sealant with rapid initial curing and a preparation method thereof. The metal organic framework MIL-101 is used to modify CaCO3, thereby greatly improving the migration rate of water vapor inside the filler. The diffusion coefficient of water vapor in the filler is 0.112 cm at 25°C and 30% relative humidity. 2 / s, an increase of 3600%, while ensuring mechanical strength; on this basis, alkoxy-terminated polydimethylsiloxane is used to further improve the curing rate. The curing depth can reach more than 1mm in 6 hours and more than 3.5mm in 24 hours, which effectively solves the problem of slow initial curing speed of existing silicone sealants. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The reagents and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods without specific conditions in the examples are implemented according to conventional conditions, such as the conditions described in the literature, books or methods recommended by the manufacturer.
[0021] Example 1
[0022] The preparation method of the metal organic framework (MOF) modified filler is as follows:
[0023] By mass, 10 parts of chromium nitrate and 4 parts of terephthalic acid are dissolved in deionized water, and 6 parts of hydrofluoric acid are slowly added. While stirring in a hydrothermal kettle, the temperature is uniformly raised to 220 degrees within 1 hour. After constant temperature reaction for 8 hours, the temperature is slowly lowered to room temperature. First wash with nitrogen, nitrogen dimethylformamide, filter and dry, and then wash with anhydrous ethanol. After filtering and drying, a metal organic framework is obtained, which is recorded as MIL-101 (Cr). Take 4 parts of MIL-101 (Cr), 1 part of aminopropyl triethoxysilane and 4 parts of heavy calcium carbonate (D50 is 150nm, specific surface area is 23m 2 / g) was ultrasonically dispersed in ether for 20 minutes, transferred to a hydrothermal reactor and heated to 150 degrees at a uniform rate within 1 hour. After constant temperature reaction for 6 hours, the temperature was uniformly reduced to 25 degrees within 8 hours. It was washed with ether and anhydrous ethanol in turn, filtered and dried to obtain MIL-101(Cr) modified calcium carbonate, recorded as MIL-101@CaCO3. The water vapor adsorption kinetic curve was tested with a water vapor adsorption instrument, and the diffusion coefficient of water vapor in MIL-101@CaCO3 was calculated to be 0.112cm at 25°C and 30% relative humidity. 2 / s.
[0024] Add 100 parts of 2000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps methoxy-terminated polydimethylsiloxane, 120 parts of MIL-101@CaCO3, 30 parts of vinyltrimethoxysilane, 2 parts of N-(-βaminoethyl)-γ-aminopropyltriethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium into a planetary machine, stir and disperse for 40 minutes under a vacuum degree of -0.095MPa to obtain a dealcoholized silicone sealant with initial rapid curing.
[0025] Example 2
[0026] The preparation method of the metal organic framework (MOF) modified filler is as follows:
[0027] By mass, 10 parts of chromium nitrate and 4 parts of terephthalic acid are dissolved in deionized water, and 6 parts of hydrofluoric acid are slowly added. While stirring in a hydrothermal kettle, the temperature is uniformly raised to 210 degrees within 1 hour. After constant temperature reaction for 9 hours, the temperature is slowly lowered to room temperature. First wash with nitrogen, nitrogen dimethylformamide, filter and dry, and then wash with anhydrous ethanol. After filtering and drying, a metal organic framework is obtained, which is recorded as MIL-101 (Cr). Take 4 parts of MIL-101 (Cr), 1 part of aminopropyl triethoxysilane and 5 parts of heavy calcium carbonate (D50 is 150nm, specific surface area is 23m 2 / g) was ultrasonically dispersed in ether for 20 minutes, transferred to a hydrothermal reactor and heated to 160 degrees at a constant speed within 1 hour, reacted at a constant temperature for 5 hours, and then cooled to 25 degrees at a constant speed within 8 hours. Washed with ether and anhydrous ethanol in turn, filtered and dried to obtain MIL-101(Cr) modified calcium carbonate, recorded as 4MIL-101@5CaCO3.
[0028] Add 100 parts of 8000cps α,ω-dihydroxypolydimethylsiloxane, 20 parts of 350cps methoxy-terminated polydimethylsiloxane, 110 parts of MIL-101@CaCO3, 20 parts of vinyltriethoxysilane, 3 parts of N-(-βaminoethyl)-γ-aminopropyltrimethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium into a planetary machine, stir and disperse for 40 minutes under a vacuum degree of -0.095MPa to obtain a dealcoholized silicone sealant with initial rapid curing.
[0029] Example 3
[0030] The preparation method of the metal organic framework (MOF) modified filler is as follows:
[0031] By mass, 10 parts of chromium nitrate and 4 parts of terephthalic acid are dissolved in deionized water, and 6 parts of hydrofluoric acid are slowly added. While stirring in a hydrothermal kettle, the temperature is uniformly raised to 230 degrees within 1 hour. After constant temperature reaction for 7 hours, the temperature is slowly lowered to room temperature. First wash with nitrogen, nitrogen dimethylformamide, filter and dry, and then wash with anhydrous ethanol. After filtering and drying, a metal organic framework is obtained, which is recorded as MIL-101 (Cr). Take 4 parts of MIL-101 (Cr), 1 part of aminopropyl triethoxysilane and 6 parts of heavy calcium carbonate (D50 is 200nm, specific surface area is 25m 2 / g) was ultrasonically dispersed in ether for 20 minutes, transferred to a hydrothermal reactor and heated to 140 degrees at a constant speed within 1 hour, reacted at a constant temperature for 7 hours, and then cooled to 25 degrees at a constant speed within 8 hours. Washed with ether and anhydrous ethanol in turn, filtered and dried to obtain MIL-101(Cr) modified calcium carbonate, recorded as 2MIL-101@3CaCO3.
[0032] Add 100 parts of 15000cps α,ω-dihydroxypolydimethylsiloxane, 25 parts of 300cps ethoxy-terminated polydimethylsiloxane, 100 parts of MIL-101@CaCO3, 30 parts of phenyltrimethoxysilane, 8 parts of γ-aminopropyltrimethoxysilane, and 0.2 parts of tetraisopropyl titanate into a planetary machine, stir and disperse for 40 minutes under a vacuum degree of -0.095MPa to obtain a dealcoholized silicone sealant with initial rapid curing.
[0033] Example 4
[0034] The preparation method of the metal organic framework (MOF) modified filler is the same as that in Example 1, and is recorded as MIL-101@CaCO3.
[0035] Add 100 parts of 20000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps ethoxy-terminated polydimethylsiloxane, 100 parts of MIL-101@CaCO3, 15 parts of methyltrimethoxysilane, 4 parts of γ-aminopropyltrimethoxysilane, 4 parts of γ-glycidyl ether propyltriethoxysilane, and 0.1 part of tetraorthotitanate into a planetary machine, stir and disperse for 60 minutes under a vacuum degree of -0.090MPa to obtain a dealcoholized silicone sealant with initial rapid curing.
[0036] Comparative Example 1
[0037] The only difference between Comparative Example 1 and Example 1 is that MIL-101@CaCO3 is replaced with commercially available nano-activated calcium carbonate Warner CCS-25i.
[0038] 100 parts of 2000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps methoxy-terminated polydimethylsiloxane, 120 parts of nano-active calcium carbonate Warner CCS-25i, 30 parts of vinyltrimethoxysilane, 2 parts of N-(-β-aminoethyl)-γ-aminopropyltriethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium were added to a planetary machine and stirred and dispersed at a vacuum degree of -0.095MPa for 40 minutes to obtain a dealcoholized silicone sealant.
[0039] Comparative Example 2
[0040] The only difference between Comparative Example 2 and Example 1 is that MIL-101@CaCO3 is replaced by the metal organic framework material MIL-101. The water vapor adsorption kinetic curve of MIL-101 was tested with a water vapor adsorption instrument, and it was calculated that the diffusion coefficient of water vapor in MIL-101 at 25°C and 30% relative humidity was 1.318 cm 2 / s.
[0041] 100 parts of 2000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps methoxy-terminated polydimethylsiloxane, 120 parts of MIL-101, 30 parts of vinyltrimethoxysilane, 2 parts of N-(-βaminoethyl)-γ-aminopropyltriethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium were added to a planetary machine and stirred and dispersed at a vacuum degree of -0.095MPa for 40 minutes to obtain a dealcoholized silicone sealant.
[0042] Comparative Example 3
[0043] The difference between Comparative Example 3 and Example 1 is that the methoxy-terminated polydimethylsiloxane is replaced by polydimethylsiloxane.
[0044] 100 parts of 2000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps polydimethylsiloxane, 120 parts of MIL-101@CaCO3, 30 parts of vinyltrimethoxysilane, 2 parts of N-(-βaminoethyl)-γ-aminopropyltriethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium were added to a planetary mill and stirred and dispersed at a vacuum degree of -0.095MPa for 40 minutes to obtain a dealcoholized silicone sealant.
[0045] Comparative Example 4
[0046] The only difference between Comparative Example 4 and Example 1 is that MIL-101@CaCO3 is replaced with unreacted MIL-101 and CaCO3.
[0047] 100 parts of 2000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps methoxy-terminated polydimethylsiloxane, 48 parts of MIL-101(Cr), 72 parts of CaCO3, 30 parts of vinyltrimethoxysilane, 2 parts of N-(-βaminoethyl)-γ-aminopropyltriethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium were added to a planetary machine and stirred and dispersed at a vacuum degree of -0.095MPa for 40 minutes to obtain a dealcoholized silicone sealant.
[0048] Comparative Example 5
[0049] The only difference between Comparative Example 5 and Example 1 is that MIL-101@CaCO3 is replaced by UIO-66@CaCO3.
[0050] The preparation method of the metal organic framework (MOF) modified filler is as follows:
[0051] By mass, 10 parts of zirconium tetrachloride and 8 parts of concentrated hydrochloric acid are dissolved in N,N-dimethylformamide, and 6 parts of hydrofluoric acid are slowly added. While stirring in a hydrothermal kettle, the temperature is uniformly raised to 80 degrees within 1 hour. After constant temperature reaction for 12 hours, the temperature is slowly lowered to room temperature. First wash with nitrogen, nitrogen dimethylformamide, filter and dry, and then wash with anhydrous ethanol. After filtering and drying, a metal organic framework is obtained, which is recorded as UIO-66 (Zr). Take 4 parts of UIO-66 (Zr), 1 part of aminopropyl triethoxysilane and 4 parts of heavy calcium carbonate (D50 is 150nm, specific surface area is 23m 2 / g) was ultrasonically dispersed in ether for 20 minutes, transferred to a hydrothermal reactor and heated to 150 degrees at a uniform rate within 1 hour. After constant temperature reaction for 6 hours, the temperature was uniformly reduced to 25 degrees within 8 hours. It was washed with ether and anhydrous ethanol in turn, filtered and dried to obtain UIO-66 modified calcium carbonate, recorded as UIO-66@CaCO3. The water vapor adsorption kinetic curve was tested with a water vapor adsorption instrument, and the diffusion coefficient of water vapor in UIO-66@CaCO3 was calculated to be 0.112cm at 25°C and 30% relative humidity. 2 / s.
[0052] 100 parts of 2000cps α,ω-dihydroxypolydimethylsiloxane, 30 parts of 100cps methoxy-terminated polydimethylsiloxane, 120 parts of UIO-66@CaCO3, 30 parts of vinyltrimethoxysilane, 2 parts of N-(-βaminoethyl)-γ-aminopropyltriethoxysilane, and 1 part of 1,3-dipropoxybis(ethoxyacetoacetyl)titanium were added to a planetary machine and stirred and dispersed at a vacuum degree of -0.095MPa for 40 minutes to obtain a dealcoholized silicone sealant.
[0053] Tests and Results
[0054] Diffusion coefficient of water vapor in different powders: The water vapor adsorption kinetic curve was tested with a water vapor adsorption instrument to obtain the relationship between the water vapor adsorption component and the adsorption time, and the diffusion coefficient D of water vapor inside different materials was calculated: At 25°C and 30% relative humidity, the diffusion coefficient of water vapor in calcium carbonate is 0.003cm 2 / s, and the diffusion coefficient in MIL-101(Cr) is 1.318cm 2 / s, and the diffusion coefficient range in MIL-101@CaCO3 is 0.091cm 2 / s~0.112cm 2 / s, and the diffusion coefficient in UIO-66(Zr) is 0.410cm 2 / s, and the diffusion coefficient in UIO-66@CaCO3 is 0.110 cm 2 / s. As shown in the following table.
[0055]
[0056] Curing speed: Curing speed is expressed as the cured thickness in a certain period of time. Under standard conditions (23°C, 50% RH), the cured thickness is measured according to Method 2: Wedge Groove Method specified in GB / T 32369.2015 and is shown in the following table. Mechanical properties test reference standard: GB 16776, tensile bond strength and elongation at maximum tensile strength are required to be cured for 28 days at (23±2)°C and relative humidity (50±5)%.
[0057]
[0058] As shown in the above table, Examples 1 to 4 can all achieve a curing depth of more than 1 mm within 6 hours, can withstand a large displacement and load in a short period of time, and can meet higher requirements such as turning over doors and windows within 6 hours after gluing, and transporting and squeezing photovoltaic modules within 6 hours after gluing. This is the biggest breakthrough of the present invention compared to traditional products.
[0059] After the active nano-calcium was used to replace the metal organic framework modified calcium carbonate (MIL-101@CaCO3) in Comparative Example 1, the 6h curing depth and 24h curing depth were greatly reduced. The 6h curing depth was less than 1mm, which could not meet the requirement of turning over the doors and windows within 6 hours after gluing. Turning over or shaking significantly would cause the sealant to crack. Both the high curing speed in the early stage (0-6h) and the later stage (6-24h) depended on the ultra-high water vapor diffusion rate of MIL-101@CaCO3 relative to the active nano-calcium. The water vapor quickly diffused along the filler inside the sealant, so that the sealant could continue to cure deep in a short time.
[0060] After the metal organic framework MIL-101 replaced the metal organic framework modified calcium carbonate (MIL-101@CaCO3) in Comparative Example 2, the 6h curing depth and 24h curing depth were greatly improved, because the water vapor diffusion rate of MIL-101 was an order of magnitude higher than that of MIL-101@CaCO3. Limited by the speed of the sealant's reaction with water vapor, the 6h curing depth was increased to 2.4mm. However, since MIL-101 had no reinforcing effect, the mechanical strength of Comparative Example 2 was very poor, and it had no practical value in the field of building sealing, and the sealant was easily broken.
[0061] After replacing alkoxy-terminated polydimethylsiloxane with polydimethylsiloxane in comparative example 3, the 6h curing depth decreased significantly. This is because alkoxy silicone oil can participate in cross-linking and has high reaction activity. Compared with the inert dimethyl silicone oil, it provides a large number of active sites. These active sites significantly improve the curing speed in the early stage of curing. The 6h curing depth is less than 1mm, which can no longer meet the requirement of turning over the doors and windows within 6 hours after gluing. Turning over or shaking significantly will cause the sealant to crack.
[0062] After replacing MIL-101@CaCO3 with unreacted MIL-101 and CaCO3 in Comparative Example 4, the 6h curing depth decreased significantly. This is because the diffusion rate of water vapor is determined by the slowest point in the transmission channel. Although the water vapor diffusion rate of MIL-101 is very fast, the diffusion rate of CaCO3 is very slow, so the water vapor diffusion is stuck on the input and output of CaCO3. The 6h curing depth is less than 1mm, which can no longer meet the requirement of turning over the doors and windows within 6 hours after gluing. Turning over or shaking significantly will cause the sealant to crack.
[0063] After replacing MIL-101@CaCO3 with UIO-66@CaCO3 in Comparative Example 5, the 6h curing depth dropped significantly. This is because UIO-66 is mainly microporous, and its diffusion rate for water vapor is lower than that of MIL-101. In addition, UIO-66 has fewer active sites for reacting with calcium carbonate, and the effect of preparing composite materials with calcium carbonate is not as good as that of MIL-101 and calcium carbonate composite materials. The 6h curing depth is less than 1mm, which can no longer meet the requirement of turning over doors and windows within 6 hours after gluing. Turning over or shaking significantly will cause the sealant to crack.
[0064] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a dealcoholized silicone sealant with rapid initial curing, characterized in that: The following steps are involved: The metal organic framework MIL-101, silane coupling agent and calcium carbonate are dispersed in an organic solvent, and then the temperature is raised to 140-160°C for reaction for 5-7 hours to obtain MIL-101@CaCO3; According to the mass parts, 100 parts of α, ω-dihydroxy polydimethylsiloxane, 20 to 30 parts of alkoxy-terminated polydimethylsiloxane, 100 to 120 parts of MIL-101@CaCO3, 15 to 30 parts of cross-linking agent, 2 to 8 parts of coupling agent and 0.1 to 1 part of catalyst are mixed and dispersed to obtain the dealcoholized silicone sealant.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the MIL-101, the silane coupling agent and the calcium carbonate is 4:0.5-1.5:4-6.
3. The preparation method according to claim 1, characterized in that: The alkoxy-terminated polydimethylsiloxane is selected from one or more of methoxy-terminated polydimethylsiloxane and ethoxy-terminated polydimethylsiloxane.
4. The preparation method according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane is 2000-20000 cps, and the viscosity of the alkoxy-terminated polydimethylsiloxane is 100-350 cps.
5. The preparation method according to claim 1, characterized in that: The preparation method of MIL-101 comprises the following steps: dissolving 10 parts of chromium nitrate and 4 parts of terephthalic acid in water by mass, adding 6 parts of hydrofluoric acid, heating to 210-230 degrees and reacting for 7-9 hours to obtain MIL-101.
6. The preparation method according to claim 1, characterized in that: The D50 of the calcium carbonate is 100-200 nm, and the specific surface area is 22-25 m 2 / g.
7. The preparation method according to claim 1, characterized in that: The crosslinking agent is selected from one or more of methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane and vinyltriethoxysilane.
8. The preparation method according to claim 1, characterized in that: The coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(-β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-glycidyl ether propyltrimethoxysilane, γ-glycidyl ether propyltriethoxysilane, epoxycyclohexyltrimethoxysilane, epoxycyclohexyltriethoxysilane, mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, isocyanatetrimethoxysilane and isocyanatetriethoxysilane.
9. The preparation method according to claim 1, characterized in that: The catalyst is selected from one or more of tetraisopropyl titanate, tetrabutyl titanate, diisopropoxydi(ethoxyacetoacetyl)titanium, di-n-butoxydi(ethoxyacetoacetyl)titanium and 1,3-dipropoxydi(ethoxyacetoacetyl)titanium.
10. An initial fast-curing dealcoholized silicone sealant, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Alcohol type adhesive and preparation method thereof
CN111763493A
Low-density high-temperature-resistant pouring sealant and preparation method thereof
CN112680177A
Metal organic framework-calcium carbonate composite crystal material and preparation method thereof
CN113461869A
High-viscosity two-component adhesive and preparation method thereof
CN116445123A
Organosilicon sealant and preparation method thereof
CN117801782A
Cited By
Low-density high-performance dealcoholized sealant and preparation method thereof
CN121182440A
